1993
DOI: 10.1111/j.1365-2249.1993.tb03373.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidic pH modulates oxygen-dependent cytotoxic responses mediated by polymorphonuclear leucocytes and monocytes

Abstract: SUMMARYIn the present study, we compared the ability of human neutrophils and monocytes to display oxygen-dependent cytotoxic responses at pH 7-4 and 6-2. Our results show that cytotoxicity induced by immune complexes (IC), zymosan, N-formyl-methionyl-leucyl-phenylalanine (FMLP) and concanavalin A (Con A) were markedly increased when they were carried out at pH 6-2 instead of pH 7-4. Cytotoxicity induced by phorbol myristate acetate (PM A), on the contrary, was significantly decreased at pH 6 2. It is notewort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… 189 , 190 In addition, Geffner et al observed an increased cytotoxic capacity of neutrophils under low pH, despite earlier reports of an inhibited respiratory burst in acidic conditions. 191 The authors hypothesize that while the production of some ROS species is inhibited, the production of others may be increased, contributing to neutrophil cytotoxicity; however, more research is needed to test this hypothesis.…”
Section: Neutrophil Function In Vitro – Effect Of Environmental Factomentioning
confidence: 99%
“… 189 , 190 In addition, Geffner et al observed an increased cytotoxic capacity of neutrophils under low pH, despite earlier reports of an inhibited respiratory burst in acidic conditions. 191 The authors hypothesize that while the production of some ROS species is inhibited, the production of others may be increased, contributing to neutrophil cytotoxicity; however, more research is needed to test this hypothesis.…”
Section: Neutrophil Function In Vitro – Effect Of Environmental Factomentioning
confidence: 99%